Elastodynamic singular points and their applications - A. D. Alawneh; R. P. Kanwal (International Journal of Mathematics and Mathematical Sciences)
Suitable singularites such as a dynamical Kelvin quadropole are defined to study the dynamical displacements set up in an infinite homogeneous and isotropic elastic medium. Approximate solutions are presented up to terms which are of higher order than those known so far.